SISTEM INFORMASI PENJUALAN PAKAIAN WANITA BERBASIS WEB (E-COMMERCE) PADA PT. BUNITOP INDONESIA - Eka Puspita Sari; Eni Pudjiarti; Helma Susanti (Jurnal Teknologi Informasi Mura, 2020)
PT. Bunitop is a national company engaged in the field of Retail Fashion, especially women's clothing located in the city of North Jakarta. Currently the sales system at PT. Bunitop is still done by manually. So it often raises the occurrence of his mistakes in data processing as well as data retrieval. To overcome the problems that occur in PT. Bunitop is required the best solution is to make an information system design using the technology that develops. Technology that develops so rapidly can be utilized well by PT. Bunitop. Utilization of the right technology will be able to improve the performance of PT. Bunitop. Long, complex and time-consuming business processes can be more efficient and can help reduce costs. E-Commerce is one of the technologies that can be applied in PT. Bunitop. E-Commerce is the answer to the demands of globalization. The implementation of E-Commerce will be able to improve the competitive advantage of PT. Bunitop. Implementation of E-Commerce requires a mature strategy that has been decided by the management of PT. Bunitop, including preparing resources of technology devices and human resources are reliable in the field of information technology. If all these things can be done well then it will be able to improve the excellence to compete.